Interakcjonistyczna interpretacja dyskursu klinicznego pomiędzy dwujęzycznym logopedą a dwujęzycznym dzieckiem - Młyński, Rafał (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2025)
The subject of the article is the analysis of free unplanned conversations (9 records) between a bilingual speech therapist and bilingual children living in the area in Chicago. The author interprets these conversations as a manifestation of clinical discourse. The methodological framework of the study is the theory of symbolic interactionism. In its perspective, the so-called negotiation of meanings in conversations between a child and a speech therapist was interpreted, also by means of the conversational analysis research method. It was used to identify microstrategies occurring in the dialogues of an adult and a child. The study showed that the subject of negotiation of meanings in the clinical discourse between a bilingual speech therapist and a child is code-switching between Polish and English. The proposed work fits into the interactionist trend of speech therapy research in relation to the bilingualism of the speech therapist and the Polish child, which fills the gap in research on Polish speech therapy. The conclusions may be useful not only for speech therapists-theoreticians, but also practitioners interested in communication with a bilingual child.